Treatment of Inguinal Lymph Node Metastases in Patients with Rectal Adenocarcinoma - Hagemans, J. A. W. (Ann Surg Oncol, 2019)
BACKGROUND: Inguinal lymph node metastases (ILNM) from rectal adenocarcinoma are rare and staged as systemic disease. This study aimed to provide insight into the treatment and prognosis of ILNM from rectal adenocarcinoma. METHODS: All patients with a diagnosis of synchronous or metachronous ILNM from rectal adenocarcinoma between January 2005 and March 2017 were retrospectively reviewed. RESULTS: The study identified 27 patients with ILNM (15 with synchronous and 12 with metachronous disease). After discussion by a multidisciplinary tumor board, 19 patients were treated with curative intent, 17 of whom underwent inguinal lymph node dissection. Of the 17 patients, 12 had locally advanced rectal cancer (LARC) with isolated ILNM, 3 had LARC and metastases elsewhere, and 2 had locally recurrent rectal cancer (LRRC). The median overall survival (OS) for all the patients treated with curative intent was 27 months [95% confidence interval (CI) 11.6–42.4 months], with a 5-year OS rate of 34%. The median OS for the patients with LARC and isolated ILNM (n = 12) was 74 months (95% CI 18.0–130.0 months), with a 5-year OS rate of 52%. All the patients with metastases elsewhere (n = 3) or LRRC (n = 2) experienced recurrent systemic disease. Eight patients were treated with palliative intent. The median OS for this group was 13 months (95% CI 1.9–24.1 months), with a 3-year OS rate of 0%. CONCLUSION: Clinicians should not consider ILNM as an incurable systemic disease. Patients with primary rectal cancer and solitary ILNM who were eligible for curative surgical treatment had a 5-year survival rate of 52%. The prognosis for patients with additional systemic metastases or LRRC is worse, and the benefit of surgery is unclear.